Hormone replacement therapies, oral contraceptives, reproductive factors and colorectal adenoma risk: a systematic review and dose–response meta‐analysis of observational studies. (22nd March 2019) - Song, J.; Jin, Z.; Han, H.; Li, M.; Guo, Y.; Guo, H.; Guo, W.; He, J.
Abstract: Aim: The association between the use of oral contraceptives and hormone replacement therapy (HRT) or other reproductive factors and the risk of colorectal adenoma (CRA) remains controversial. Our study aimed to review the evidence by conducting a dose–response meta‐analysis to investigate this association. Methods: We searched PubMed and Embase databases for relevant studies published until May 2017. Traditional and dose–response meta‐analyses were conducted. Sensitivity analysis was performed to evaluate the robustness of the results. Cumulative meta‐analysis was used to assess the risk of different oral contraceptive formulations or generations. Results: A total of 19 observational studies, with 21 923 CRA cases and 1 030 711 participants, were included in the meta‐analysis. Ever HRT use showed a potential inverse association with CRA risk [relative risk (RR) 0.83, 95% CI 0.70–1.00]. The dose–response meta‐analysis further demonstrated that HRT use could reduce CRA risk. Compared with no HRT use, the predicted RRs were 0.82 (95% CI 0.67–0.99), 0.76 (95% CI 0.59–0.98) and 0.77 (95% CI 0.62–0.96) for 3, 6 and 9 years of HRT use, respectively. All other factors were not statistically significantly associated with CRA risk. Conclusions: This study indicated that only HRT use might reduce the risk of developing CRA. Any advice regarding HRT use to prevent CRA should be tailored to the individual risks and potential benefits. Large, well‐designed prospective studies with long‐term follow‐up are required to further clarify the aetiology of CRA.